Significance of lipid profile in antenatal patients for early diagnosis of preeclampsia - Khan, Fiza Ali; Naz, Tallat; Azhar, Arfa; Abid, Fatima; Memon, Noorunnisa; Jafri, Tariq Kamal (Pakistan Journal of Physiology, 2020)
Objective: To determine the importance of Lipid Profile in antenatal patients presenting with hypertriglyceridemia for early diagnosis of Preeclampsia at the time of delivery at tertiary care hospital located in Karachi. Methodology: This cross-sectional research was done from 01- April 2013 to 01 October 2013 (6 months), at Department of Obstetrics & Gynecology, JPMC, Karachi. A total of 105 antenatal patients with age limit 18-40 years, single viable pregnancy with gestational age corresponding to>20 to 40thweek. Data was analyzed by SPSS version 16, Mean + SD, frequencies and percentages were calculated. Chi-square test was applied where necessary and P value less than 0.05 considered as significant. Results: The mean age of the subjects was 29.67 ± 5.13 with parity 1.21 ± 0.67 and the gestational period 34.67 ± 3.53 weeks. The mean value of serum Triglyceride was 285 ± 40 mg/dL (201 -372 mg/dL). The frequency of preeclampsia in hypertriglyceridemia subjects was 14.29% (n=15). Eclampsia was identified in (13.33%, n=2), placental abruption occurred in (20%, n=3), HELLP syndrome was observed in (13.33%, n=2) and preterm deliveries happened in (26.67%, n=4) patients. The age of mother, fetal age, parity as well as level of triglycerides in blood serum has influence on incidence of preeclampsia and its outcomes. Conclusion: Our results signify the importance of fasting lipid profile in screening antenatal patients for early diagnosis and prevention of future complications in the mother as well as the child.